(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Volodina Anastasia Vsevolodovna – post-graduate student, faculty of linguistics, history of literature dpt. Moscow State University of M.V. Lomonosov. Abstract. The article focuses on the works by William Faulkner, the plot of which cover the Civil War period – the novel «Undefeated» (1938), stories «Sermon victory» (1932) and «My Grandmother Millard, General Forrest and the Battle of Harrykin Creek» (1943). The image of the war is compared with the works of W. Faulkner and T.N. Page – in his apologetic southern collection of stories «The old Virginia or Mars Chan and Other Stories» (1887). It is studied how in the works of Faulkner the typical of the works of that era of Reconstruction concept of the «Lost Case» is refracted, according to which the North-South war was an attack of the barbarian Northerners on a supreme civilization, populated by noble cavaliers-Southerners. This article shows the transformation of Faulkner’s topos of classical southern military novel: devotion of the freed slave to his master, Yankees invasion of the plantation, love against the backdrop of the war, a heroic death. Faulkner deprives the uniqueness of the image of the war, his characters do not match the roles, or match them partially. Faulkner reduces the heroic pathos by means of irony, and travesty, refuting the myth cultivated by decades of great and glorious war. Key words: W. Faulkner, T.N. Page, Civil War of the USA, southern military novel.